Prevention of Clostridioides difficile in hospitals: A position paper of the International Society for Infectious Diseases. (January 2021) - Doll, Michelle; Marra, Alexandre R.; Apisarnthanarak, Anucha; Al-Maani, Amal Saif; Abbas, Salma; Rosenthal, Victor D.
Abstract: Clostridioides difficile infection is an increasing presence worldwide. Prevention is multipronged, reflecting a complex and evolving epidemiology. Multiple guidelines exist regarding the prevention of C. difficile infection in healthcare settings; however, existing guidelines do not address C. difficile in low- and middle-income countries (LMIC). Nevertheless, the prevalence of C. difficile in LMIC likely parallels, if not exceeds, that of high-income countries, and LMIC may experience additional challenges in C. difficile diagnosis and control. A panel of experts was convened by the International Society for Infectious Diseases (ISID) to review the current state of C. difficile infections globally and make evidence-based recommendations for infection prevention that are broadly applicable.